A pilot study on the effect of D-allulose on postprandial glucose levels in patients with type 2 diabetes mellitus during Ramadan fasting - Japar, Salimah; Fukunaga, Kensaku; Kobayashi, Toshihiro; Imachi, Hitomi; Sato, Seisuke; Saheki, Takanobu; Ibata, Tomohiro; Yoshimura, Takafumi; Kim, Lam Soh; Swee, Leong Ong; Muhamed, Zamri; Murao, Koji (BMC, 2022)
Background: During Ramadan fasting, postprandial hyperglycemia is commonly observed after iftar (break of fast at sunset) meal. D-allulose is a rare sugar and is reported to have several health benefits, including the suppression of increase in postprandial glucose levels. This study investigates whether D-allulose (a C-3 epimer of D-fructose) improves the postprandial glucose in patients with type 2 diabetes mellitus (T2DM) during Ramadan. Methods: This was a pilot, prospective single-arm study design that was conducted for 10 consecutive days; 5 days of control and 5 days of consumption. The primary outcome was postprandial peak glucose levels. During the consumption period, 8.5 g of D-allulose was consumed by the participants before iftar meal. Postprandial glucose was measured using a continuous glucose monitoring system. Results: A total of 12 participants completed the study. Significant lower (p < 0.01) postprandial glucose values and the glucose incremental area under the curve (iAUC) were observed from 0 to 180 min during the consumption period compared to the control period. The consumption period demonstrated significantly higher percentages of time in which glucose values were found in the target range (p = 0.0032), and when the glucose levels above the target range were reduced (p = 0.0015). Conclusions: The supplementation with D-allulose has the potential to improve postprandial hyperglycemia in patients with T2DM after iftar during Ramadan. Further studies are needed to confirm these findings.